Oedipus unbound: selected writings on rivalry and desire - Girard, René (Stanford University Press, 2004)
From the novelistic experience to the Oedipal myth -- Oedipus analyzed -- Symmetry and dissymmetry in the myth of Oedipus -- Doubles and the pharmakos in Lʹevi-Strauss, Frye, Derrida and Shakespeare -- The myth of Oedipus, the truth of Joseph